The effect of crude alcoholic extract of Withania somnifera leaves in experimentally induced arthritis in mice - *Huda F. Hasan (University of Thi-Qar Journal of Science, 2019)
The alcoholic extract 70% of the leaves of Withania Somnifera was dried and percentage of extract 8.3 were used.Incomplete freunds adjuvant was used to induce arthritis in mice 0.1ml of this adjuvant was injected in the right tarsaljoint. The mice were divided into four groups, the first group were treated with alcoholic extract 500mg/kg body weight(T1), the second group was treated with diclofenac sodium 3mg/kg body weight (T2) and third group was treated withdistilled water (T3), the fourth group used as a control group (T4) non induced non treated.Vernier calipers was used formeasuring the diameter of the joint. The mice in T1group showed a significant decrease in the diameter of tarsal jointof right leg as compared with mice in T2, T3 and T4 groups. The hematological results of mice in T1 group showedsignificant increase as compared with T4 group. While inT2 and T3 groups showed a significant decrease as comparedwith T4 group .The histological results showed that the joint of mice in T1 group showed no inflammatory response inthe membrane of joint. The joint of mice in T2 group showed inflammatory cell infiltration while the joint of mice in T3group showed fibrous connective tissue proliferation with mononuclear cell infiltration in the membrane of the joint .